PENGARUH KUALITAS PELAYANAN DAN TARIF TERHADAP KEPUASAN KONSUMEN HOTEL AMANDA HILLS BANDUNGAN - Rifka Ayu Rusdiana; Agus Hermani DS (Universitas Diponegoro, 2017)
One of the company's expectations in winning the hearts of consumers is to obtain the satisfaction of the consumer. Based on preliminary studies found several problems in the Amanda Hills Hotel in poor service quality and prices are expensive. Some of these problems have an impact on revenue Amanda Hills Hotel. This study aims to determine the effect of service quality and prices on consumer satisfaction who stay at Amanda Hills Hotel. Data collection technique used purposive sampling with a sample of 100 consumers. Quantitative data were analyzed using SPSS version 16. The analytical method used is correlation, linear regression, t-test, F and determination.The results show the positive influence and significant correlation between quality of service and prices on consumer satisfaction Amanda Hills Hotel either partially or simultaneously. From these two variables shows that the service quality has the most impact on customer satisfaction at 66.2%, compared to a variable price that affects customer satisfaction by 29.6%. Advice to enhancing consumer satisfaction, in terms of service quality by increase the speed of employees in serving, facilitate submission of complaints, the appearance of the building, exterior and interior more attractive, completeness improved facilities, enhanced cleanliness and tidiness of the rooms and environment. While in terms of price rates can be set not too much different from competitors.